2004
DOI: 10.4141/a03-085
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and breed differences for feed efficiency, growth, and body composition traits of young beef bulls

Abstract: breed differences for feed efficiency, growth, and body composition traits of young beef bulls. Can. J. Anim. Sci. 84: 177-185. Genetic associations between feed efficiency, growth, and live ultrasound measured body composition traits were studied in purebred beef bulls of six breeds in Ontario bull test stations from 1991 to 2000. Feed traits included average daily feed intake (FI), feed conversion ratio (FCR), and residual feed intake [feed intake adjusted for production alone (RFIp) or production and backfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
124
4
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 22 publications
63
124
4
12
Order By: Relevance
“…The significant negative relationship between sire EPD DMI with carcass meat proportion is consistent with the findings in dairy and late-maturing beef breed cross comparisons, whereby Holstein/Friesian cattle were shown to have higher intake and lower carcass meat proportion than similarly managed Charolais cattle (Keane et al, 1990;McGee et al, 2005). Furthermore, Schenkel et al (2004) reported a significant genetic correlation of 0.24 between feed intake and ultrasonically measured back fat thickness, which is consistent with the increases in scanned fat depth and carcass fat proportion per unit increase in sire EPD DMI observed in the present study. Clarke et al (2009) reported an increase in DM intake with increasing sire EPD DMI .…”
Section: Economic Index and Performancesupporting
confidence: 91%
“…The significant negative relationship between sire EPD DMI with carcass meat proportion is consistent with the findings in dairy and late-maturing beef breed cross comparisons, whereby Holstein/Friesian cattle were shown to have higher intake and lower carcass meat proportion than similarly managed Charolais cattle (Keane et al, 1990;McGee et al, 2005). Furthermore, Schenkel et al (2004) reported a significant genetic correlation of 0.24 between feed intake and ultrasonically measured back fat thickness, which is consistent with the increases in scanned fat depth and carcass fat proportion per unit increase in sire EPD DMI observed in the present study. Clarke et al (2009) reported an increase in DM intake with increasing sire EPD DMI .…”
Section: Economic Index and Performancesupporting
confidence: 91%
“…Animal performance and feed efficiency Overall ADG, initial BW and DMI of the bulls used in the current study are within the ranges observed by Schenkel et al (2004), Lancaster et al (2009) and Kelly et al (2011) for growing beef bulls offered an energy dense, high concentrate diet. The current study has shown that for growing beef bulls, weight and growth accounted for a substantial proportion (0.79) of the variation in RFI and that high RFI bulls had a 14% greater DMI than low RFI bulls for the same level of production.…”
Section: Discussionsupporting
confidence: 68%
“…Correlations found in this work were consistent to the ones reported in literature (Schenkel et al, 2004;Nkurumah et al, 2004), evidencing that average daily gain and body weight are variables that influence the intake by the animal. According to Tedeschi et al (2006) cattle that have genetic potential for faster growth, at the same growth stage, are the ones that consume more food in order to satisfy the increases on nutrient requirement.…”
Section: Resultssupporting
confidence: 92%